(untitled) (Palimpsesto, 2021)
The present investigation addresses the possibility of thinking a Philosophy of Latin American History based on the characteristics that marked the Chilean social outbreak of October 2019, placing special emphasis on the break of historical meaning that this means and the emergence of an incipient new consciousness . For this, I will focus mainly on Arturo Andrés Roig, fundamentally for his importance within Latin American thought during the 20th century, and because they are part of a critical constellation regarding the philosophy of Latin American history, and whose contributions it is possible to analyze those aspects that justify the above approach. To this end, I have established the following dimensions as spaces for dialogue between the author’s contributions and the understanding of the process in question: 1) History and philosophy of history; 2) We; 3) Temporality; and 4) Coloniality, domination and Liberation.